Development of portable wireless parking sensor device - Mansor, Nuratiqa Natrah; Jamaluddin, Muhammad Herman; Shukor, Ahmad Zaki; Abdul Razib, Syaiful Asyraf (Penerbit Akademia Baru, 2023)
Parking is regarded as one of the most difficult aspects of driving a vehicle since it is a stressful and confusing situation, even for a competent driver. Therefore, there are many parking sensor devices designed to facilitate the user's search for a parking spot. The ultrasonic sensor was used for the construction of the parking sensor gadget because it is more resistant to environmental conditions than other sensors. This project's objective is to create a portable, wireless parking sensor device by utilizing ultrasonic sensor features in SolidWorks, Proteus, and Arduino. The prototype of the SolidWorks 3D portable wireless parking sensor gadget has to be rigorously tested at parking spaces for vehicles several times in order to depict the actual environment accurately. To facilitate a seamless vehicle detecting procedure, it was necessary that the prototype be strong and durable. After implementing 2 different types of ad-hoc networks, the outcomes showed that the nRF24L01 module normally offers two types of alternatives, either in mesh routed form or Point-to-Point link (PtP). However, the latter is most recommended to gain higher performance and more configurable